ANALYSIS OF ALKALINE AND ALKALINE EARTH METALS IN STANDARD SAMPLES BY LIQUID ELECTRODE PLASMA OPTICAL EMISSION SPECTROMETER - Hidayanto, Eko; Yamamoto, Takashi; Kawai, Jun (JURNAL SAINS DAN MATEMATIKA, 2010)
ABSTRACT---Sodium,  potassium and calcium  in  standard sample solution  were analyzed with  a portable analyzer  of  liquid  electrode  plasma optical emission spectrometer  (LEP-OES) to assess  its validity for  quantitative  analysis. Reproducibility  and sensitivity  were  investigated  using  different  disposal  sample chip  and applied voltage.  ln  the applied voltage of  800 V, there is no  increasing period  of emission  intensity by  consecutive measuremenl  and  the  relative  standard deviation  among  chips  was  less  than  20%.  The sensitivity  of  emission  intensity  for  Na  and K  were  proportional  to  the  applied  voltage, but  Ca  wasexponential.  The  sensitivity  was  different  by  kinds  of  element  and  applied  voltage.  According  to  its reproducibility,  the spectrometer would  be used  for quantitative  analysis.Permalink : http://ejournal.undip.ac.id/index.php/sm/article/view/3115